Different physical forms of one diet fed to growing pigs induce morphological changes in mandubular glands and local leptin (Ob) production and receptor (ObR) expression. Issue 6 (23rd March 2016) - Cappai, M. G.; Dall'Aglio, C.; Sander, S. J.; Ratert, C.; Dimauro, C.; Pinna, W.; Kamphues, J.
Summary: The physical form of the diet plays an important role for morphological adaptations of organs in the gastrointestinal tract. It was hypothesized that different physical forms of one diet could exert extra‐enteric effects, under local and systemic neuroendocrine regulation. Gross morphology, fresh mass and cytoarchitecture of mandibular glands (MG) were studied in growing pigs fed with one diet processed under four different physical forms. Four dietary treatments were offered for 4 weeks to 32 growing pigs (initial BW: 8.30 ± 0.83 kg) allotted into 4 experimental groups: FP, finely ground pellet (dMean, 0.46 mm); CM, coarsely ground meal (dMean, 0.88 mm); CP, coarsely ground pellet (dMean, 0.84); CE, coarsely ground extruded (dMean, 0.66). Conventional and immuonohistochemical techniques were used to immunolocalize, in particular, leptin (Ob) and its receptor (ObR). A significant effect was observed on the relative mass of the MG, depending on the diet (p < 0.03) and on the BW (p < 0.04), with no interactions (diet*BW). The immunohistochemical reactions for Ob and ObR showed a marked positivity in the MG from the group fed with the CM diet, displaying Ob‐positive acinar cells and ObR‐positive cells in the striated ducts, together with endocrine‐like cells. The intensity of chromogenic reactions positively testing to ObR was used to evaluate the cytoarchitecture of the MG and its possible correlations. Pearson's correlation coefficient resulted to positively link (p < 0.0001) the ObR expression with the absolute mass of MG in the 61.1% of pigs. The physical form of the diet is related to extra‐enteral effects, inducing changes in gross and microscopic morphology of the MG in the growing pig. The local production of Ob and the expression of the respective ObR in the striated duct cells shed a new light on the mitogenic activity of Ob in extra‐enteral organs, like the MG, in relation to the physical form of the diet.